2011
DOI: 10.1158/1078-0432.ccr-10-1996
|View full text |Cite
|
Sign up to set email alerts
|

Copy-Neutral Loss of Heterozygosity at the p53 Locus in Carcinogenesis of Esophageal Squamous Cell Carcinomas Associated with p53 Mutations

Abstract: Purpose: LOH at the p53 locus has been reported to be associated with esophageal squamous cell carcinogenesis. The aim of this study is to identify potential mechanisms resulting in LOH around the p53 locus in its carcinogenesis.Experimental Design: We investigated 10 esophageal cancer cell lines and 91 surgically resected specimens, examining them for LOH at the p53 locus on chromosome 17. We examined the p53 gene by using microsatellite analysis, comparative genomic hybridization (CGH), FISH, and single-nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…An important intrinsic factor that could possibly explain the difference in responsiveness is selective advantage due to intratumoral genetic heterogeneity, as was recently shown for renal cell carcinoma as a proof of principle. 27 This heterogeneity could be caused by microsatellite instability, 28 loss of heterozygosity, 29,30 and copy number variations. 31,32 Extrinsic factors include differences in oxygenation levels and cancer cell-stroma interactions.…”
Section: Discussionmentioning
confidence: 99%
“…An important intrinsic factor that could possibly explain the difference in responsiveness is selective advantage due to intratumoral genetic heterogeneity, as was recently shown for renal cell carcinoma as a proof of principle. 27 This heterogeneity could be caused by microsatellite instability, 28 loss of heterozygosity, 29,30 and copy number variations. 31,32 Extrinsic factors include differences in oxygenation levels and cancer cell-stroma interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The exact regulation of p53-mediated cell cycle arrest or apoptosis is complex and depends on the cellular context and specific stress stimuli (8). Inactivation of the p53 pathway is observed in most human cancers, with mutations in p53 occurring in at least 50% of all tumors (9). Interestingly, in addition to the lack of tumor suppressive functions, p53 mutants gain oncogenic activities contributing to carcinogenesis and drug resistance (10).…”
mentioning
confidence: 99%
“…Recent analysis showed that LOH without copy number changes at the p53 locus was observed in p53 mutant esophageal squamous cell carcinomas. This copy-neutral LOH might be the major mechanism for inactivation of the intact allele in esophageal squamous cell carcinogenesis associated with p53 mutations [87]. Our data suggest that copy-neutral LOH, occurring because of CIN, might be the major mechanism for inactivation of the intact allele in esophageal squamous cell carcinogenesis associated with p53 mutations.…”
Section: Relationship Between P53 Mutations and Dna Aneuploidymentioning
confidence: 62%